(untitled) (Research, Society and Development, 2021)
The use of sftwares in the health areas has achieved prominence in the last few years. However, data on the quantity and structural characteristics of those who adressed the development of children in the first years of life and the neurobiological, social and environmental determimants that may interfere in this process are still scarce. This study aimed to carry out a documentary investigation in the national and international context on articles available in indexed and applications for mobile devices that can contribute as guidance for parents on child development. This is documentary, descriptive sutdy with a qualitative approach, based on the survey of indexed databases and applications for smartphones with Android and iOS operating system. For the reasearch for theoretical-scientific content and applications, an exploratory reasearch was carried out in three stages: 1) bibliographic surveys using the in scientific databases Pubmed, via Medical Literature Analysis and Retrievel System Online (MEDLINE), Cochrane Library e Virtual Health Library (VHL); 2) the survey of application for mobile devices Google Play and App Store virtual stores, in the Android and iOS platform, respectively; 3) data organization. 199 articles were found with the descriptors, however, only 2 articles stood out on the eficiency in the use of text messages and telephone means on pregnant and postpartum guidelines. On the App Store platform a total of 425 applications were found, however, only 9 met the inclusion and exclusion criteria, while on Google Play 1149 were found and only 29 met the criteria. Therefore it is necessary to develop applications for mobile devices with more didatic, interactive proposals and with scientif content about guidance for parents on child development.